Highly efficient and stable planar perovskite solar cells with reduced graphene oxide nanosheets as electrode interlayer. (March 2015) - Yeo, Jun-Seok; Kang, Rira; Lee, Sehyun; Jeon, Ye-Jin; Myoung, NoSoung; Lee, Chang-Lyoul; Kim, Dong-Yu; Yun, Jin-Mun; Seo, You-Hyun; Kim, Seok-Soon; Na, Seok-In
Abstract: We demonstrate a simple solution and room-temperature processed reduced graphene oxide (RGO) as a novel hole-transporting material (HTM) to guarantee highly efficient and highly stable CH3 NH3 PbI3 perovskite solar cells (PeSCs). The effects of RGO HTM are systemically investigated in terms of PeSC efficiency, PeSC stability, morphology of perovskite film, recombination dynamics, and charge-transport through CH3 NH3 PbI3 /HTM interface. The resultant PeSC with a planar configuration of glass/ITO/RGO/CH3 NH3 PbI3 /PC61 BM/bathocuproine (BCP)/Ag exhibits improved device efficiency (maximum PCE of 10.8%) with high reproducibility than those of the reference devices using conventional PEDOT:PSS and GO HTMs. Also, the RGO-based PeSCs show highly desirable device stability in comparison to the PEDOT:PSS PeSCs. Graphical abstract: Highlights: Highly efficient and stable perovskite solar cells are developed using solution and room-temperature processed RGO. The resultant PeSC with planar architecture depicts a superior device efficiency (10.8%) to PEDOT:PSS- and GO-based solar cells. The use of RGO HTMs with the inherent passivation ability greatly extended the cell-operation time compared to PeSCs with PEDOT:PSS.